PROBLEMS OF UKRAINIAN ENERGY AND THEIR SOLUTIONS - G. Fyliuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper studies current situation at the Ukrainian electric power industry. The problems which prevent development of the industry under current conditions are analyzed. The problems of the cross-subsidization are exposed. The ways of the problems solutions are offered.